Morfofunktional aspects of influence of employments of kallanetik on the women's senior age group organism. - Nikolenko O.V; Ugolkov G.M; Seryogin V.N; Navtikov A.E (Kharkov National Pedagogical University, 2011)
For the study of influence of employments of kallanetik on an organism of the group of woman at the age of 50-60 age with the low level of motion activity was tested during a half of year. It is shown in the process of half-year research that after the systematic training the changes developed in work of cardiovaskular and respiratory systems shows up in economization of their functions, physical capacity and rising of restoration processes speed flowing after the physical loading.